Medial insufficiency in postoperative weight-bearing radiographs in supination-external rotation type 4 bimalleolar ankle fractures: is the Lauge-Hansen classification insufficient in predicting medial soft tissue damage? - Yüce, Ali; Yerli, Mustafa; Bayraktar, Tahsin Olgun; Karslıoglu, Bulent; İmren, Yunus and Dedeoğlu, Süleyman Semih and Kır, Mustafa Çağlar and Gürbüz, Hakan (The European Research Journal, 2021)
Objectives: According to the Lauge-Hansen classification, supination external-rotation (SER) type 4 fractures should be accompanied by medial malleolar fracture or deltoid ligament injury. The aim of the study was to investigate medial insufficiency rates in postoperative weight-bearing radiographs in SER type 4 bimalleolar fractures. Methods: The files of the patients who were operated with the diagnosis of SER type 4 bimalleolar ankle fracture between 2017-2020 were evaluated retrospectively. Thirty-seven cases (15 males and 22 females) were included in the study. The data based on the evaluation of the weight-bearing radiographs of the patients taken in the postoperative 1st year were examined statistically. Results: The injury mechanism was sports injury in 17 (45.9%) cases, traffic accidents in 8 (21.6%) cases, falling in 9 (24.3%) cases, and falling from height in 3 (8.2%) cases. The preoperative tibiofibular distance was 6.05 ± 1.86 mm, and the postoperative tibiofibular distance was 4.19 ± 0.40 mm (p = 0.001). The preoperative tibiofibular overlap was 5.03 ± 2.93 mm, and the postoperative tibiofibular overlap was 8.62 ± 1.04 mm (p = 0.001). The postoperative medial clear space was 4.11 ± 0.57 mm. Postoperative medial clear space of 5 mm and higher was determined in 7 (18.9%) cases. Conclusions: In SER type 4 bimalleolar fractures with a large medial malleolar fragment fracture, weight-bearing radiographs may show an increase in medial clear space. This means that a medial malleolar fracture in bimalleolar fractures may be also accompanied by deltoid ligament injury. The Lauge-Hansen classification system may be insufficient to identify a medial ligament injury.